Association between extrauterine growth restriction and changes of intestinal flora in Chinese preterm infants. (5th March 2019) - Zhang, J.; Dai, Y.; Fan, S.; Zhang, K.; Shuai, C.; Bian, X.; Hui, L.; Wu, Z.; Zhang, J.; Guo, Z.; Deng, F.; Guo, M.
Abstract: The aim of the study was to investigate any association between extrauterine growth restriction (EUGR) and intestinal flora of <30-week-old preterm infants. A total of 59 preterm infants were assigned to EUGR ( n =23) and non-EUGR ( n =36) groups. Intestinal bacteria were compared by using high-throughput sequencing of bacterial rRNA. The total abundance of bacteria in 344 genera (7568 v. 13, 760; P <0.0001) and 456 species (10, 032 v. 18, 240; P <0.0001) was significantly decreased in the EUGR group compared with the non-EUGR group. After application of a multivariate logistic model and adjusting for potential confounding factors, as well as false-discovery rate corrections, we found four bacterial genera with higher and one bacterial genus with lower abundance in the EUGR group compared with the control group. In addition, the EUGR group showed significantly increased abundances of six species ( Streptococcus parasanguinis, Bacterium RB5FF6, two Klebsiella species and Microbacterium ), but decreased frequencies of three species (one Acinetobacter species, Endosymbiont _of_ Sphenophorus_lev and one Enterobacter _species) compared with the non-EUGR group. Taken together, there were significant changes in the intestinal microflora of preterm infants with EUGR compared to preterm infants without EUGR.